PENERAPAN MEDIA FLASH CARD UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DENGAN MODEL APACIN PADA SISWA KELAS 1 - Mahardika, Wulan Putri; Rokhman, Fathur; Wasino; Sumartiningsih, Sri; Yuwono, Agus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Reading is one step in the learning process. Students will master skills, develop reading techniques, and learn to better understand what they have read. However, based on facts in the field, it shows that students' ability to read pronunciation is still not fluent, students still write sentences with incomplete words, and there are still students who have difficulty putting words together. Given these problems, researchers will use the APACIN (Observe, Think, Analyze, Create and Information) learning model. This learning development is carried out with the help of flash cards. Data collection techniques in this research used the methods: Observation, Interviews, Tests, and Documentation. The subjects of this research are grade 1 students. The initial reading ability assessment instrument uses assessment guidelines consisting of four aspects, namely: pronunciation, intonation, fluency, voice clarity. The data analysis technique in this research uses comparative analysis. This research was carried out in 2 cycles using the PTK flow according to Kemmis and Mc Taggart (1988) where each cycle consists of stages which include 1) planning; 2) implementation; 3) observation; and 4) reflection. At the time of the research there were 63% of the 30 students who did not have initial reading skills. Based on these results, it can be concluded that the measure of success of this research is considered successful if 80% of the total number of students in this research can read the beginning correctly.